2008
DOI: 10.1111/j.1442-9071.2008.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of ocular cystinosis

Abstract: A 31-year-old woman who presented with photophobia was found to have bilateral corneal and conjunctival crystal deposition. Ocular cystinosis was diagnosed upon observation of typical crystals and lack of systemic involvement. In vivo confocal microscopy confirmed crystal deposition of the corneas and conjunctivae bilaterally. Optical coherence tomography showed stromal hyper-reflectivity due to crystals within the corneal stroma. Transmission electron microscopy of the conjunctiva demonstrated pathognomonic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In vivo confocal microscopy demonstrated irregularly oriented widely distributed ovoid, fusiform, and needle-shaped crystalline deposits with a length ranging between 10 between 140 mm in corneal stroma in nephropathic and ocular cystinosis. [17][18][19][20] In multiple myeloma, immunoglobulins were shown to deposit at every level of the cornea in histopathologic and electron microscopic studies. 21 Using in vivo confocal microscopy, the crystal deposits appeared as discrete hyperreflective globules distributed randomly within the corneal epithelium and anterior stroma.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo confocal microscopy demonstrated irregularly oriented widely distributed ovoid, fusiform, and needle-shaped crystalline deposits with a length ranging between 10 between 140 mm in corneal stroma in nephropathic and ocular cystinosis. [17][18][19][20] In multiple myeloma, immunoglobulins were shown to deposit at every level of the cornea in histopathologic and electron microscopic studies. 21 Using in vivo confocal microscopy, the crystal deposits appeared as discrete hyperreflective globules distributed randomly within the corneal epithelium and anterior stroma.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there are contradictory data on the stromal pattern of corneal crystal deposition. Most of the studies describe that the majority of the crystals is located in the anterior or in the posterior stroma [9,10], while some case reports describe the main involvement of the middle layer [2,5]. Previous histopathological and clinical studies confirmed that crystal deposition begins at the anterior and peripheral part of the cornea and spreads posteriorly and centrally with aging [11,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Nephropathic or infantile cystinosis is the most frequent (95% of cases) and the most severe phenotype of the disease [5]. It is characterized by renal Fanconi syndrome, which begins in infancy, usually from 6 to 12 months of age [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the patients in these studies had nephropathic cystinosis, not the milder ocular cystinosis presented in our case report. In a case report by Kocabora et al [6], these crystals were described as variable in size and shape, being square, oblong, or rhomboid at 0.5-2 μm in length. This is comparable to the pathology specimen from our case report, which showed oblong crystals of varying size on TEM.…”
Section: Discussionmentioning
confidence: 99%